Bmp5 Mutation Alters miRNA Expression During Embryonic External Ear Development. Issue 8 (29th November 2022) - Liu, Wei; Lin, Lin; Jin, Shengyang; Yang, Qinghua; Jiang, Haiyue
Abstract : Abstract: To understand the changes in gene regulation and expression of MicroRNA (miRNA) involved in external mouseear embryonic development after point mutation of the Bmp5 gene, the outer ear tissues of developed E15.5 and E17.5 mouse embryos were obtained using a Bmp5 short ear mouse model, and the changes in miRNA expression profiles were detected. Changes in miRNA expression in the experimental and control groups were identified during Bmp5 short ear mouse embryo development at E15.5 and E17.5. GO and Kyoto Encyclopedia of Genes and Genomes functional annotations were performed on differentially expressed miRNAs. Multiple signal pathways related to miRNA expression were enhanced during the development of E15.5 and E17.5 embryos of Bmp5 short-ear mice. Based on the basic characteristics of miRNAs, this study aimed to determine the differential expression of miRNAs in Bmp5 short-ear mice during the development of external ear embryos using advanced sequencing techniques. The results showed differences in some key regulatory miRNA changes after point mutations in the Bmp5 gene. This study provides new insights into the mechanism by which miRNAs regulate the development of the external mouse ear. Changes in miRNA expression profiles can also provide clues for studying the biological regulatory mechanism of external ear embryonic development.